Study on Development Potency of Coastal Tourist Object in Majene District, West Sulawesi, Indonesia - Nur Adyla Suriadi; Muhammad Arsyad; Arifuddin Akil; Nurlaela; Muhammad Arafat Abdullah; Ade Mulawarman (Politeknik Pariwisata Makassar, Indonesia, 2022)
Majene Regency is one of the regencies in the province of West Sulawesi with a length of 125 km beach located on the coast of West Sulawesi stretch out from South to North with an area of 947.84 Km on the west side of Sulawesi Island, so that it is famous regency for its beautiful beaches. However, it has not the existence of good tourism planning according to the potency of coastal tourism, resulted in the potency of the tourism sector in improving the regional economy is not optimal. The purpose of this study was to determine the potency of beach tourism in developing tourism attractions. The research used a survey method with analytical techniques using scoring for internal and external potency and a combination of both. The results indicate that the internal potency with high classification is Barane Beach, Dato Beach, and Munu Beach with a score of 18, external potency with high classification is Barane Beach with a score of 23, and the combined potency of internal and external with high classification is Barane Beach, so the priority of developing tourism objects that need to be done is Barane Beach, Dato Beach and Munu Beach respectively.